Understanding the usability of an mHealth tool to support medication adherence schedules in newly diagnosed tuberculosis patients : a mixed-methods research study - Mostert, Sonja (University of Pretoria, 2025)
Thesis (PhD (Psychology))--University of Pretoria, 2024.